2011
DOI: 10.1007/s00213-011-2572-1
|View full text |Cite
|
Sign up to set email alerts
|

Impulsive behaviour induced by both NMDA receptor antagonism and GABAA receptor activation in rat ventromedial prefrontal cortex

Abstract: RationalePrevious work has demonstrated a profound effect of N-methyl-d-aspartic acid receptor (NMDAR) antagonism in the infralimbic cortex (IL) to selectively elevate impulsive responding in a rodent reaction time paradigm. However, the mechanism underlying this effect is unclear.ObjectivesThis series of experiments investigated the pharmacological basis of this effect in terms of excitatory and inhibitory neurotransmission. We tested several pharmacological mechanisms that might produce the effect of NMDAR a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

8
79
0
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 97 publications
(89 citation statements)
references
References 44 publications
(58 reference statements)
8
79
0
1
Order By: Relevance
“…Our findings of positive correlations of the BIS-11 total impulsivity score with Glu/tCr and a trend for a negative correlation with GABA adds further support for the involvement of glutamatergic and GABAergic mechanisms in the expression of impulsivity (Hayes et al, 2014;Jupp et al, 2013;Murphy et al, 2012 ). In a group-wise correlation analyses, the Glu/tCr correlations hold for the BPD group.…”
Section: Discussionsupporting
confidence: 72%
See 1 more Smart Citation
“…Our findings of positive correlations of the BIS-11 total impulsivity score with Glu/tCr and a trend for a negative correlation with GABA adds further support for the involvement of glutamatergic and GABAergic mechanisms in the expression of impulsivity (Hayes et al, 2014;Jupp et al, 2013;Murphy et al, 2012 ). In a group-wise correlation analyses, the Glu/tCr correlations hold for the BPD group.…”
Section: Discussionsupporting
confidence: 72%
“…Despite these studies, Hayes argues that there is still a lack of research on GABA in the general context of impulsivity (Hayes et al, 2014). In rodents, Murphy et al recently reported implications for glutamatergic and GABAergic mechanisms in the infralimbic cortex in the expression of impulsivity (Murphy et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…Activation of the mPFC is required for suppression of impulsive action (Dalley et al, 2011;Murphy et al, 2012) and cocaine-seeking behavior (Koya et al, 2009;LaLumiere et al, 2012). Our observation that 5-HT 2C R knockdown in the mPFC resulted in elevated impulsive action and cocaine cue reactivity suggests that loss of the 5-HT 2C R inactivates the mPFC suppression circuit to drive aggregate expression of these behaviors.…”
Section: Discussionmentioning
confidence: 85%
“…Preclinical studies suggest that reductions in or lower levels of GABA are associated with greater impulsivity (Boy et al 2011; Murphy et al 2012; Paine et al 2011). We have previously shown that [ 11 C]Ro15‐4513 is sensitive to GABA levels, and since it is an inverse benzodiazepine agonist, lower levels of GABA would be associated with higher [ 11 C]Ro15‐4513 binding.…”
Section: Discussionmentioning
confidence: 99%
“…As the main inhibitory neurotransmitter in the human brain, the role of GABAergic functioning in impulsivity is attracting attention with growing preclinical evidence supporting its involvement (Hayes et al 2014). For instance, a GABA agonist and antagonist in the prefrontal cortex of rats increased and reduced, respectively, impulsive responses in the 5‐choice serial reaction time task (Murphy et al 2012; Paine et al 2011). GABA A receptor binding is lower in the anterior cingulate cortex of high‐impulsive rats compared with low‐impulsive rats and is inversely correlated with impulsive responding (Jupp et al 2013).…”
Section: Introductionmentioning
confidence: 99%